PARTISIPASI MASYARAKAT DALAM PENANGGULANGAN STUNTING DI KECAMATAN SUKATANI KABUPATEN PURWAKARTA - Muhammad Hasbi As-Siddiq; Ane Permatasari (Universitas Jenderal Ahmad Yani, 2024)
Based on the Purwakarta District Health Office in 2022, the stunting rate in Sukatani District reached 8.81%. The contributing factors include: parenting, malnutrition and the environment. The program carried out by the Sukatani Puskesmas in an effort to overcome this stunting, namely: blood tablet program, immunization, posyandu for toddlers and pregnant women classes. Forms of community participation in stunting prevention in Sukatani District, namely: labor, skills and social participation. The purpose of the research was conducted to find out how community participation in stunting prevention in Sukatani District. This research uses a qualitative method, which is research that aims to understand human or social phenomena by creating a comprehensive picture that can be presented in words. The results showed that some parents still lack knowledge about stunting due to their low level of education. There is a community movement consisting of PKK mothers to assist the puskemas in implementing the program. The author provides suggestions that can be used as reference material for the Sukatani District Health Center to further improve the planning of the stunting program, improve communication relations with the community so that it can facilitate the delivery of information about the stunting program. The community must feel more aware or concerned about the dangers of stunting, follow the program that has been made by the puskemas, so that the stunting rate in Sukatani District can decrease.